IFPRI-Ethiopia hosts half-day seminar on food systems transformation - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
On September 18, 2025, IFPRI-Ethiopia convened a half-day seminar at the ILRI Campus in Addis Ababa, bringing together partners and representatives from the U.S. Embassy, USDA, EU-Ethiopia, Ministry of Agriculture (MoA), Ministry of Finance (MoF), Ethiopian Public Health Institute (EPHI), Ministry of Health (MoH), PSI, Addis Ababa University, and other key stakeholders.